Hemodialysis Specific Nutrition Screening Tool (HD-NUT) - Validity and reliability assesment for Turkey - Coskun, Ayfer Beyaz; Elibol, Emine; Genc, Fatih; Kockaya, Pinar (Aran Ediciones, S L, 2025)
Background and aims: this study aimed to evaluate the validity and reliability of the Hemodialysis Specific Nutrition Screening Tool (HD-NUT), a new hemodialysis-specific nutrition screening tool for Turkey. Methods: HD-NUT was compared for assessing malnutrition with the Malnutrition Universal Screening Tool (MUST) and Subjective Global Assessment (SGA) in 165 adult patients across two dialysis units. Nutritional status was evaluated using anthropometric measurements and the nurse's opinion was assessed via a survey. Results: HD-NUT was found to be more sensitive than MUST in identifying increased risks of malnutrition and providing dietary guidance. The Cramer V coefficient was 0.445 between MUST and HD-NUT, and 0.487 between SGA and HD-NUT, and indicating compatibility with variables in other screening tools. Significant agreements were found between MUST and HD-NUT (Kappa = 0.409, p = 0.000) and between SGA and HD-NUT (Kappa = 0.290, p = 0.000). Conclusions: HD-NUT is a valid and reliable nutritional screening tool when used by specialist nurses experienced in dialysis units for hemodialysis patients in Turkey.
Herramienta de detección nutricional específica para hemodiálisis (HD-NUT): evaluación de la validez y la fiabilidad para Turquía
Keywords: Hemodialysis; Malnutrition; MUST; SGA; HD-NUT